2009
DOI: 10.1038/nature07967
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of insect and human dengue virus host factors

Abstract: Dengue fever (DF) is the most frequent arthropod-borne viral disease of humans, with almost half of the world's population at risk of infection1. The high prevalence, lack of an effective vaccine, and absence of specific treatment conspire to make DF a global public health threat1, 2. Given their compact genomes, dengue viruses (DENV 1-4) and other flaviviruses likely require an extensive number of host factors; however, only a limited number of human, and an even smaller number of insect host factors have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
360
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 334 publications
(368 citation statements)
references
References 30 publications
7
360
0
1
Order By: Relevance
“…The advent of siRNA technology and the availability of genome-wide siRNA libraries have been useful in identifying host factors required for influenza virus, an NS RNA virus, and several positive-strand RNA viruses, as well as HIV (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The lack of similar studies with other NS RNA viruses has limited the understanding of the role of host cell factors in replication of these viruses.…”
mentioning
confidence: 99%
“…The advent of siRNA technology and the availability of genome-wide siRNA libraries have been useful in identifying host factors required for influenza virus, an NS RNA virus, and several positive-strand RNA viruses, as well as HIV (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The lack of similar studies with other NS RNA viruses has limited the understanding of the role of host cell factors in replication of these viruses.…”
mentioning
confidence: 99%
“…Permissivity to flavivirus infection is determined by many different hostcell factors that may either be required for efficient infection of mammalian and arthropod cells (host susceptibility factors, HSFs) or restrict infection in certain cells (host resistance factors, HRFs) (Krishnan et al, 2008;Sessions et al, 2009). For example, .40 candidate HSFs have been identified that are required for growth of the mosquito-borne dengue virus (DENV) type 2 in arthropod, but not in mammalian, cells (Sessions et al, 2009). It is largely unknown which viral determinants are responsible for host tropism and vector specificity, i.e.…”
mentioning
confidence: 99%
“…Many flaviviruses have evolved unique strategies to adapt to the special requirements of their specific target cells (reviewed recently by Fernandez-Garcia et al, 2009). Permissivity to flavivirus infection is determined by many different hostcell factors that may either be required for efficient infection of mammalian and arthropod cells (host susceptibility factors, HSFs) or restrict infection in certain cells (host resistance factors, HRFs) (Krishnan et al, 2008;Sessions et al, 2009). For example, .40 candidate HSFs have been identified that are required for growth of the mosquito-borne dengue virus (DENV) type 2 in arthropod, but not in mammalian, cells (Sessions et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this goal, and to better characterize the innate immune response against the virus, several approaches have been followed using either Aedes or Drosophila models. These approaches include genome wide RNAi interference screen in Drosophila, 6 whole-genome microarray in Aedes aegypti 7 and evolutionary dynamics of immune-related genes and pathways in disease-vector mosquitoes. 8 Importantly, the antimicrobial Toll pathway was shown to control Dengue virus infection in Aedes aegypti 9-11 but was not required for Wolbachia mediated dengue virus interference in Drosophila.…”
Section: Introductionmentioning
confidence: 99%